Konstruksi Model Sosialisasi Hukum Berbasis Kearifan Lokal Kepada Yayasan Penyelenggara Pendidikan Dalam Penyesuaian Anggaran Dasar - Bahmid; Hamidah Sidabalok; Dewi Sartika; Renita Dewi; Rifqah Anisa Heni Nasution (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2023)
Non-compliance by organs of educational foundations in Asahan Regency with orders to adjust the articles of association for foundations that existed before the enactment of Law Number 28 of 2004 concerning amendments to Law Number 16 of 2001 concerning Foundation. This is because it is not in accordance with local wisdom in Asahan Regency. Therefore, it is important to do research on directing legal compliance in the form of outreach regarding existing problems associated with local wisdom. The research method used is empirical juridical with an effectiveness approach. From the results of the study, it shows that the socialization of local wisdom is very effective in providing interpretation to the community. This is because the organs of the foundation understand why it is important to make adjustments to the articles of association.